2021
DOI: 10.1039/d1dt00820j
|View full text |Cite
|
Sign up to set email alerts
|

Sterically hindered phenanthroimidazole ligands drive the structural flexibility and facile ligand exchange in cyclometalated iridium(iii) complexes

Abstract: Cyclometalated Ir(iii) complexes with bulky 2-arylphenanthroimidazole ligands possess tunable optical properties and demonstrate unusually high reactivity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 61 publications
0
16
0
Order By: Relevance
“…55 For example, the combination of bulky phenanthroimidazole-based ligands (containing two additional fused rings as compared to the parent benzimidazole system) and an ancillary aromatic β-diketone or pyridylphenanthroimidazole around the iridium(III) ion did not lead to the improvement of absorption in the visible region, [56][57][58] but surprisingly enhanced the reactivity of the complexes, which dissociated on the surface of the standard titania photoanodes. 59 Based on these studies, we have concluded that phenanthroimidazole is the edge case (at least for imidazole-based cyclometalating ligands) and further extension of the conjugated π-system in this part of the ligands can only lead to a further decrease in the stability of the octahedral complexes. It is also evident that all the above approaches to the development of perfect iridium dyes offer limitations because separation of strong light-harvesting characteristics from the side effects has not been mastered.…”
Section: Introductionmentioning
confidence: 93%
“…55 For example, the combination of bulky phenanthroimidazole-based ligands (containing two additional fused rings as compared to the parent benzimidazole system) and an ancillary aromatic β-diketone or pyridylphenanthroimidazole around the iridium(III) ion did not lead to the improvement of absorption in the visible region, [56][57][58] but surprisingly enhanced the reactivity of the complexes, which dissociated on the surface of the standard titania photoanodes. 59 Based on these studies, we have concluded that phenanthroimidazole is the edge case (at least for imidazole-based cyclometalating ligands) and further extension of the conjugated π-system in this part of the ligands can only lead to a further decrease in the stability of the octahedral complexes. It is also evident that all the above approaches to the development of perfect iridium dyes offer limitations because separation of strong light-harvesting characteristics from the side effects has not been mastered.…”
Section: Introductionmentioning
confidence: 93%
“…The synthesis does not require the use of palladium-catalyzed cross-coupling reactions. , Fine tuning of the emission properties can be achieved by the introduction of electron-withdrawing/-donating groups in (ii) and (iii) and the bulkiness of the final complex can be monitored, notably by the substitution in (i). Yet, the investigations of this ligand have been limited to the modification of the phenyl group, ,,, ,, the replacement of the benzimidazole by a π-extended imidazole ring, and a modification of the substitution of secondary amine with charge carrier units ,, or different alkyl chains or aryl groups, to name a few. ,, …”
Section: Introductionmentioning
confidence: 99%
“…50,51 Fine tuning of the emission properties can be achieved by the introduction of electron-withdrawing/-donating groups in (ii) and (iii) and the bulkiness of the final complex can be monitored, notably by the substitution in (i). Yet, the investigations of this ligand have been limited to the modification of the phenyl group, 36,38,49,[39][40][41][42][43][44]47,48 the replacement of the benzimidazole by a π-extended imidazole ring, 52 and a modification of the substitution of secondary amine with charge carrier units 37,42,45 or different alkyl chains or aryl groups, to name a few. 6,46,53 For example, the iridium(III) complex featuring the cyclometalated ligand 1-methyl-2-phenylbenzimidazole and a phenanthroline as an ancillary ligand has been reported to display an emission centered at 528 nm with a photoluminescence quantum yield (PLQY) of 51% in deaerated CH 2 Cl 2 .…”
Section: ■ Introductionmentioning
confidence: 99%
“…Though the vast majority of C^N-cyclometalated iridium(III) chlorides are μ-chloro-bridged dimers [ 27 ], it is well documented that the increase in the steric pressure (for example, induced by phenanthroimidazole-based cyclometalated ligands) destabilizes the iridium octahedron and rare monomeric trigonal–bipyramidal chlorides can be isolated [ 28 , 29 , 30 , 31 , 32 , 33 ]. Given that the perimidine core is sterically more bulky than nitrogen-containing parts of cyclometalated ligands commonly used in iridium(III) chemistry (in most cases, pyridine ring in 2-phenylpyridines), and is rather similar to the phenanthroimidazole unit, the formation of the above monomeric species becomes possible.…”
Section: Resultsmentioning
confidence: 99%